Two new species of Stenaelurillus Simon, 1886 from India (Araneae: Salticidae: Aelurillina) - Prajapati, Dhruv A.; Murthappa, Prashanthakumara S.; Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2016)
Stenaelurillus digitus sp. nov. and Stenaelurillus gabrieli sp. nov. are described from India. New distributional records for Stenaelurillus albus Sebastian et al., 2015 and Stenaelurillus lesserti Reimoser, 1934 and maps for these species are given.